How Luther regards Moses: the lectures on Deuteronomy - Hopgood, Miles (Refo500 academic studies, 2023)
Cover -- Title Page -- Copyright -- Table of Contents -- Abbreviations -- Conventions -- Introduction -- 1. Why Deuteronomy? Understanding the Purpose of the Lectures -- 1.1 Introduction -- 1.2 Luther and the Wittenberg Movement -- 1.3 Developments in Luther's Thought during the Wartburg Period -- 1.3.1 Pre-Wartburg: On the Babylonian Captivity of the Church -- 1.3.2 Wartburg: The Misuse of the Mass -- 1.3.2.1 Defining Scriptural Authority -- 1.3.2.2 The Universal Priesthood -- 1.3.2.3 Sacrifice in the Lex Christi -- 1.4 Luther and Karlstadt: A Comparison -- 1.4.1 Karlstadt's On the Removal of Images -- 1.4.2 Exemplars or Aberrations? -- 1.4.2.1 Karlstadt's Regarding Vows -- 1.4.2.2 Luther: Letters and Treatises from the Wartburg -- 1.5 Conclusions and Looking toward Deuteronomy -- 2. What has Homer to do with Moses? Moses as Author of Scripture -- 2.1 Introduction -- 2.2 Luther's Concept of Moses as Author in the Lectures -- 2.2.1 Human Agency and Divine Authorship -- 2.2.1.1 Obstacles in Language and Translation -- 2.2.1.2 Moses's Agency as Author of Deuteronomy -- 2.2.2 The Author as Creative and Imaginative Genius -- 2.2.3 The Mosaic Style of Writing -- 2.2.3.1 Constructing and Structuring the Text -- 2.2.3.2 Modes of Speech and their Meaning -- 2.2.3.3 Repetition, Remembrance, and Repetition as Rhetorical Style -- 2.3 The Role of Moses as Author -- 2.4 Conclusion -- 3. Fountain and Father of all Prophets: Moses as Prophet of Faith -- 3.1 Introduction -- 3.2 Moses and the Prophet as Teacher -- 3.2.1 Conflicts over Prophecy in the Reformation -- 3.2.1.1 Müntzer on Prophecy -- 3.2.1.2 Luther contra Müntzer -- 3.2.2 Deuteronomy as Moses's Lectures -- 3.2.3 Moses's Pedagogical Compassion -- 3.3 The Teachings of Moses in Deuteronomy -- 3.3.1 The Role of Experience in Luther's Hermeneutic -- 3.3.1.1 Conscience as the Location of Experience.